2023
DOI: 10.1088/2399-1984/acca56
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the preparation and assembly of two-dimensional plate materials in Langmuir–Blodgett films: a review

Abstract: In recent years, two-dimensional (2D) plate materials have become the most attractive class of candidate materials with a wide range of potential applications due to their unique structural characteristics and physicochemical properties. Starting from graphene, 2D plate materials have become a large family with many members and diverse categories. Especially in the recent past years, we have made some significant breakthroughs in the field of 2D materials. Langmuir-Blodgett (LB) technology is an advanced techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…At intermediate compression values, a granular morphology is observed that exhibits empty (dark) regions interspersed with graphene-covered (bright) areas (Figure c). This distribution is expected when hard disks are undergoing a jamming transition, and the observed loose packing represents the highest achievable compression state in the absence of disk deformation and has been observed for the assembly of 2D materials at the air–water interface. , …”
Section: Resultsmentioning
confidence: 96%
“…At intermediate compression values, a granular morphology is observed that exhibits empty (dark) regions interspersed with graphene-covered (bright) areas (Figure c). This distribution is expected when hard disks are undergoing a jamming transition, and the observed loose packing represents the highest achievable compression state in the absence of disk deformation and has been observed for the assembly of 2D materials at the air–water interface. , …”
Section: Resultsmentioning
confidence: 96%